The effect of transformational leadership on innovative work behavior by sharing knowledge as a mediating variable - Rini Sarianti; Lisa Ramadhani (Jurnal Kajian Manajemen dan Wirausaha, 2023)
This study aims to analyze: (1) the effect of transformational leadership on sharing knowledge (2) the effect of sharing knowledge on innovative work behavior (3) the effect of transformational leadership on innovative work behavior (4) the effect of transformational leadership on innovative work behavior through knowledge sharing. This research is a causal research. The population of this study are all employees at PT. Telkom Indonesia (Tbk) Witel West Sumatra with a total of 58 people. The sampling technique was taken using total sampling where the number of samples is equal to the total population, namely 58 people. Collecting data using a questionnaire with a Likert scale. The analysis technique used is through SmartPLS 4 software. The results of data processing in this study show that: (1) transformational leadership has a positive and significant effect on knowledge sharing among employees of PT. Telkom Indonesia (Tbk) Witel West Sumatra (2) Knowledge sharing has a positive and significant effect on innovative work behavior among employees of PT. Telkom Indonesia (Tbk) Witel West Sumatra (3) transformational leadership has a positive and significant effect on innovative work behavior of employees of PT. Telkom Indonesia (Tbk) Witel West Sumatra (4) transformational leadership has a positive and significant effect on innovative work behavior through sharing knowledge with employees of PT. Telkom Indonesia (Tbk) Witel West Sumatra.Keyword: transformational leadership, innovative work behavior, knowledge sharing